Factors Associated with and Notions Concerning Stress of the Administration and Academic Personnel - Prose Ivy G. Yepes; Jude A. Duarte (Philippine Association of Institutions for Research, Inc., 2012)
Noticeably, stress has affected the performance of the university's manpower which result to sagging morale in the workplace. Thus this study evaluated the factors associated with and notions concerning stress of the administration and academic personnel of SLSU. A descriptive-survey method was employed to gather data from the 125 respondents using a Stress Audit instrument adopted from Miller and Smith (1993). The data gathered were consolidated and statistically analyzed using percentages and Pearson-r. On the whole, the administrative and academic personnel of SLSU had manifested serious susceptibility to stress sources and stress symptoms which were significantly affected by the academic personnel's age profile, and slightly affected by the length of service of both academic and administrative staff. The academic personnel's number of office designations had affected both their perspective on stress sources and symptoms. It can be deduced that the SLSU administrative and academic personnel's notions concerning stress sources and symptoms vary due to the nature and gravity of the tasks they perform. Therefore, it is recommended that a comprehensive "Welfare Administration Program" for the SLSU personnel be implemented to reduce health risks caused by stress and to promote the welfare and well-being of all SLSU employees.